Study of Type 2 Diabetes Mellitus Patients Attending Urban Health Training Centre of Community Medicine Tertiary Care Hospital, Maharashtra - Suchita N Kawale; Manjusha A Shinde; Harshal T Pandve; Prashant S Shinde (National Journal of Community Medicine, 2020)
Introduction: Diabetes mellitus is a heterogeneous group of diseases, characterized by chronic hyperglycemia, resulting from environmental and genetic causes. Aim - To study the cases of type 2 diabetes mellitus attending urban health training centre of community medicine department of tertiary care hospital, Maharashtra.